IMPLEMENTASI STRATEGI PEMBELAJARAN SCAFFOLDING MELALUI LESSON STUDY PADA MATA KULIAH ANALISIS REAL - Wahidin Ashari, Nur; Salwah; A, Fitriani (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2016)
The type of this research is a descriptive. Subjects in this study were students on VII semester of academic year 2015-2016. This research implement scaffolding learning strategy through lesson study in real analysis subject matter, which was held in September and October 2015. The scaffolding learning strategies present the theorems to the students, difficult but systematic and thereafter students are given assistance to complete. Results of the study are (i) the learning activities of students using scaffolding learning strategies through lesson study on the analysis of real subjects each cycle are increase. (ii) the ability of students to prove theorems in real analysis are increase for each cycles. Originally a student in proving the theorem need help lecturers constantly but at the end of the cycle, the students become more independent in proving theorems. (iii) the confidence and activity of the students are increase to. Students become more confident when appointed by lecturers working on the white board.